Analysis Of Distortion For Islamic Terms Used In English Textbooks For Islamic University Students Based On Al-Faruqi’s Concept - Setiawan, Edi (Journal Research of Social Science, Economics, and Management, 2023)
Islam taught by Rasulullah S.A.W, reached its golden age and became a reference to world civilization during the Umayyah, Abbasiah, and other dynasties which finally collapsed during the Ottoman Turks (1924 AD) which later made western civilization a reference point for civilization in this world. Under these conditions a big idea emerged to restore the glory of Muslims, especially in the field of science, the concept was known as the Islamization of knowledge, by Syed Naquib Al-Attas and Ismail Raji Al-Faruqi. From the two scientists, Al-Faruqi specifically made the concept of Islamization of knowledge in the context of teaching English by making a guide book "Toward Islamic English". This then encouraged the author to examine three books, "Islamic English" authored by Professor Muhibbin Syah, "English for Islamic Studies" by Professor Djamaluddin Darwis, and "English for Islamic Studies" by Doctor Kardimin, to study what Islamic materials are integrated into learning English and whether the textbooks apply the guide to avoid the distortion of Islamic terms made by Al-Faruqi or not. The final results show, of the three books, the content of "aqidah" is more than the content of "shariah" and "akhlak” and the three books also found distortions in transliteration and translation of Islamic terms in English.